National ethnic and racial disparities in disciplinary practices: A contextual analysis in American secondary schools. (June 2019) - Ksinan, Albert J.; Vazsonyi, Alexander T.; Ksinan Jiskrova, Gabriela; Peugh, James L.
Abstract: Previous research has documented ethnic/racial disparities in the implementation of school discipline, including exclusionary practices. The current study focused on ethnic/racial disparities in four types of school exclusionary policies through the Civil Rights Data Collection (2013–2014) based on 15, 901 middle and 18, 303 high schools from the United States. Consistent with an ecological model of multi-contextual influences, school- and region-level characteristics were tested in a multi-level analytic model. Sex, disability status, and ethnicity/race were estimated at level 1, with the following school-level predictors at level 2: proportion of youth eligible for free or reduced lunch, school size, diversity (percentage of students of different ethnicities/races in school), urban/suburban/rural locale, and region (Northeast, Midwest, South, and West). Findings provided robust evidence of persistent discrepancies in disciplinary practices across ethnic/racial groups. Specifically, African American students and students self-identifying as two or more races were found to be at greater risk for school discipline actions across all disciplinary measures in both middle and high schools. Regarding school-level variables, students from lower SES schools and smaller schools were at greater risk for some disciplinary measures. Unexpected findings were found for regional differences, as Midwestern schools had significantly higher rates for most disciplinary measures as compared to Southern schools. Moreover, ethnic/racial discrepancies were moderated by school-level characteristics, such that African American students and students self-identifying with two or more races were more likely to be disciplined at low SES schools and at schools with greater diversity.